Integrating natural non-pharmaceutical therapies into medical tourism: a dynamic health portrait-driven model for proactive older adult health and public health services - Liu, Mingyu; Wang, Boyuan (Frontiers in Public Health, 2025)
In the face of the dual challenges of global population aging and the high prevalence of chronic diseases, traditional healthcare systems are facing severe tests in terms of resource allocation and service accessibility. This study focuses on the synergistic integration of natural non-pharmacological therapies (NPT) and medical tourism (MT), exploring their potential as an innovative service model to enhance the proactive health management capabilities of older adult patients with chronic conditions and optimize public health management. MT integrates global high-quality medical resources with personalized services (such as traditional Chinese medicine, physical therapy, psychological therapy, hydrotherapy, nutritional management, and other diversified NPT) to provide older populations with comprehensive health interventions encompassing sports activities and rehabilitation, nutritional dietary management, social interaction and mental health, emotional adjustment, and physical therapy. A systematic review of the literature revealed that this model has achieved significant results in promoting early intervention for chronic diseases, improving the physical and mental health of the people over 65, and enhancing social functioning and quality of life. However, it still has limitations in terms of standardized construction (especially the integration of traditional Chinese medicine), the depth of interdisciplinary collaboration, evidence-based research on long-term health benefits, and the development of intelligent and precise services. Future development should focus on establishing a multidisciplinary NPT-MT service standard system, strengthening interdisciplinary evidence-based research (especially long-term effect assessments), and exploring intelligent algorithm-driven dynamic health management pathways. This study provides theoretical basis and practical references for policymakers to optimize healthy aging strategies, healthcare institutions to innovate service models, and related industries to develop integrated health tourism products.